2016
DOI: 10.1002/jbm.a.35751
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the BSA protein adsorption and bacterial adhesion of Al‐alloy surfaces after creating a hierarchical (micro/nano) superhydrophobic structure

Abstract: Bacterial adhesion and subsequent biofilm formation on metals such as aluminum (Al) alloys lead to serious issues in biomedical and industrial fields from both an economical and health perspective. Here, we showed that a careful manipulation of Al surface characteristics via a facile two-steps superhydrophobic modification can provide not only biocompatibility and an ability to control protein adsorption and bacterial adhesion, but also address the issue of apparent long-term toxicity of Al-alloys. To find out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 87 publications
(147 reference statements)
1
30
0
Order By: Relevance
“…Besides, good anticorrosion properties would possibly originate from the stable Ta 2 O 5 protective films formed on substrata . From a biomimetic viewpoint, the Ta‐modified micro/nano‐structured surface would facilitate osseointegration since it has better mimicked the natural bone structures . Furthermore, its surface roughness belonged to the “moderately rough” category, which would favor bone‐to‐implant contact .…”
Section: Discussionmentioning
confidence: 99%
“…Besides, good anticorrosion properties would possibly originate from the stable Ta 2 O 5 protective films formed on substrata . From a biomimetic viewpoint, the Ta‐modified micro/nano‐structured surface would facilitate osseointegration since it has better mimicked the natural bone structures . Furthermore, its surface roughness belonged to the “moderately rough” category, which would favor bone‐to‐implant contact .…”
Section: Discussionmentioning
confidence: 99%
“…The overnight bacterial suspensions were diluted with fresh and sterilized MHBM to adjust the half-McFarland standards by measuring the absorbance at 625 nm. 35 The specimens were sterilized with ethanol 75% and were dried near the flame. Then, unmodified and modified membranes were immersed inside the test tubes comprising a suspension of bacteria and were incubated for 10 days.…”
Section: Protein Adhesion Testmentioning
confidence: 99%
“…Increased protein adsorption could also indicate higher biocompatibility They confirmed that biofilm formation could be prevented by modifying surface characteristics via coatings or by introducing anti-adhesion properties. Additionally, low surface energy coupled with nano textured morphology of the biomaterial surface could reduce bacterial attachment [54].…”
Section: Characterization Of P(3ho-3hd-3hdd) Solvent Cast Filmsmentioning
confidence: 99%